2022
DOI: 10.3389/fbioe.2022.928799
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Functionalized in Biomaterials for Bone Tissue Engineering: A Prominent Role in Osteoimmunomodulation

Abstract: With the development of bone tissue engineering bio-scaffold materials by adding metallic ions to improve bone healing have been extensively explored in the past decades. Strontium a non-radioactive element, as an essential osteophilic trace element for the human body, has received widespread attention in the medical field due to its superior biological properties of inhibiting bone resorption and promoting osteogenesis. As the concept of osteoimmunology developed, the design of orthopedic biomaterials has gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 196 publications
0
22
0
Order By: Relevance
“…7A) Compared to BG, a high OPN expression with PSr6 in pre-osteoblast agreed with the ALP activity results, further validating the Sr-stimulated maturation of osteoblastic cells. 40,41 The biomineralization analysis through ARS assay micrographs show the increased distribution of stained mineralized regions in PSr6 (Fig. 7B).…”
Section: Papermentioning
confidence: 95%
“…7A) Compared to BG, a high OPN expression with PSr6 in pre-osteoblast agreed with the ALP activity results, further validating the Sr-stimulated maturation of osteoblastic cells. 40,41 The biomineralization analysis through ARS assay micrographs show the increased distribution of stained mineralized regions in PSr6 (Fig. 7B).…”
Section: Papermentioning
confidence: 95%
“…31,32 Strontium (Sr) is also a crucial trace element in the human body, mainly existing in bone tissue. 33,34 Due to its specific "dual effect" of promoting osteogenesis and inhibiting the osteoclast activity, Sr has been extensively used in biomaterial modification. 35 Besides, recent research reported that Sr could also promote M2 macrophage activation.…”
Section: Introductionmentioning
confidence: 99%
“…Sr 2+ promotes the survival, proliferation, and differentiation of osteoblasts, but it could lead to the apoptosis of osteoclasts, thus reducing the rate of bone resorption. 23 In addition, Sr 2+ stimulates collagen and non-collagen synthesis. Continuously releasing Sr 2+ through a tissue interface implant is superior to oral administration because it continues to stimulate bone formation while minimizing the potential side effects associated with large oral doses of Sr 2+ .…”
Section: Introductionmentioning
confidence: 99%